2022
DOI: 10.3390/ijms23158059
|View full text |Cite
|
Sign up to set email alerts
|

Boron Derivatives Accelerate Biofilm Formation of Recombinant Escherichia coli via Increasing Quorum Sensing System Autoinducer-2 Activity

Abstract: Boron is an essential element for autoinducer-2 (AI-2) synthesis of quorum sensing (QS) system, which affects bacterial collective behavior. As a living biocatalyst, biofilms can stably catalyze the activity of intracellular enzymes. However, it is unclear how boron affects biofilm formation in E. coli, particularly recombinant E. coli with intracellular enzymes. This study screened different boron derivatives to explore their effect on biofilm formation. The stress response of biofilm formation to boron was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The biofilm biomass of E. coli was determined using crystal violet as reported previously [ 5 , 45 ]. The seed liquid of the two strains with a concentration of 10 7 CFU/mL was inoculated into a 96-well plate, and it was cultured at 37 °C for 24 h. Each group was set with 6 wells as parallel, and the wells without inoculated strains were regarded as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biofilm biomass of E. coli was determined using crystal violet as reported previously [ 5 , 45 ]. The seed liquid of the two strains with a concentration of 10 7 CFU/mL was inoculated into a 96-well plate, and it was cultured at 37 °C for 24 h. Each group was set with 6 wells as parallel, and the wells without inoculated strains were regarded as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 4% glutaraldehyde was added to a 12-well plate and placed in a refrigerator at 4 °C overnight. Then, the 4% glutaraldehyde was removed, and the biofilm adsorbed on the glass slide was stained with SYBR Green I dye for 30 min, which was used for fluorescence inversion microscopy (Eclipse TS100, Nikon, Tokyo Metropolis, Japan) and laser focusing scanning microscopy (LEXTOLS4000, Olympus, Tokyo, Japan) observation according to the method of Chen and Zhu et al [ 5 , 50 ]. In addition, ethanol was used to dehydrate the biofilm fixed with 4% glutaraldehyde and freeze-dried for scanning electron microscope (Regulus-8100, Hitachi, Tokyo, Japan) observation [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of various boron derivatives (H 3 BO 3 , NaBO 2 , Na 2 B 4 O 7 , and NaBO 3 ) to E. coli culture medium, stimulated the biofilm formation by increasing AI-2 QS system activity. [16] AI-2 is synthesized from 4,5-dihydroxy-2,3-pentanedione (DPD) via cyclized form pro-AI-2. Although reaction of pro-AI-2 with borate (B(HO) 4 À ) produces AI-2, pro-AI-2 can give other related diester signaling molecules if boron is depleted.…”
Section: Introductionmentioning
confidence: 99%
“…These authors found that adhesion to the oral environment cannot be controlled by structural means. Chen et al [8] found that boron (an essential element for autoinducer-2 synthesis of quorum sensing systems) promoted biofilm formation by upregulating the expression levels of biofilm-related genes, improving the autoinducer-2 activity and increasing the secretion of extracellular polymeric substances by Escherichia coli.…”
mentioning
confidence: 99%